PENGARUH KECEPATAN PUTARAN BLOWER EVAPORATOR TERHADAP KINERJA AC MOBIL - Wardika, Wardika; Sunanto, Sunanto; Sugara, Ferry; Mulya, Yusha Tri (Jurnal Teknologi Terapan, 2018)
The air distribution system in the room has the task of flowing cold or hot air into the room, a comfortable room condition is at a temperature of 24˚C. This study aims to determine the effect of the speed of the blower rotation on the performance of the car's AC. The cooling system in the vehicle, uses a blower to distribute cold air produced by the evaporator. Many choices of speed blowers to distribute cold air. In this study using variations in the speed value of blowers. Blower speed greatly affects the room / cabin temperature. Avoiding excessive energy consumption or inefficient energy consumption is indicated by a decrease in the COP from a cooling machine. After research obtained efficiency data for low blower rotation speed of 73.36%, medium rotation of 72.86%, and high rotation of 72.83%. But the fastest cooling of the cabin uses a high speed blower rotation. Keywords: Performance, Car AC, Speed Blower, Temperature